2011
DOI: 10.1186/1472-6963-11-28
|View full text |Cite
|
Sign up to set email alerts
|

Development and applicability of Hospital Survey on Patient Safety Culture (HSOPS) in Japan

Abstract: BackgroundPatient safety culture at healthcare organizations plays an important role in guaranteeing, improving and promoting overall patient safety. Although several conceptual frameworks have been proposed in the past, no standard measurement tool has yet been developed for Japan.MethodsIn order to examine possibilities to introduce the Hospital Survey on Patient Safety Culture (HSOPS) in Japan, the authors of this study translated the HSOPS into Japanese, and evaluated its factor structure, internal consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 7 publications
6
56
1
1
Order By: Relevance
“…Saúde Pública 2016; 32(11):e00115614 | www.ensp.fiocruz.br/csp pend on further exploratory factor analyses and removal of problematic items until achieving a satisfactory model. The authors chose not to do so for the following reasons: (1) this study, the first to investigate the psychometric properties of the Portuguese version of the HSOPSC for use in Brazil, is exploratory in nature and, accordingly, it is advisable to test this version in other larger Brazilian samples; (2) development of the HSOPSC theoretical model involved thorough, well-documented studies by AHRQ, indicating caution and parsimony in the use of empirical results and changes to the original model after comprehensive tests, including qualitative studies, and use of larger samples; and (3) HSOPSC has been used widely in diverse socio-economic and cultural contexts and at different levels of monitoring and concern with quality care and patient safety, at differing stages of development, with results that mostly confirm the original model 12,17,18,19,20 , thus suggesting that HSOPSC is an instrument which enables different levels of patient safety culture to be detected and compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saúde Pública 2016; 32(11):e00115614 | www.ensp.fiocruz.br/csp pend on further exploratory factor analyses and removal of problematic items until achieving a satisfactory model. The authors chose not to do so for the following reasons: (1) this study, the first to investigate the psychometric properties of the Portuguese version of the HSOPSC for use in Brazil, is exploratory in nature and, accordingly, it is advisable to test this version in other larger Brazilian samples; (2) development of the HSOPSC theoretical model involved thorough, well-documented studies by AHRQ, indicating caution and parsimony in the use of empirical results and changes to the original model after comprehensive tests, including qualitative studies, and use of larger samples; and (3) HSOPSC has been used widely in diverse socio-economic and cultural contexts and at different levels of monitoring and concern with quality care and patient safety, at differing stages of development, with results that mostly confirm the original model 12,17,18,19,20 , thus suggesting that HSOPSC is an instrument which enables different levels of patient safety culture to be detected and compared.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability testing evaluated the extent to which results obtained by the Brazilian version of HSOPSC could be replicated. In order to allow for comparison with other validation studies 11,12,13,14,15,16,17,18,19,20,21,22 , the reliability of HSOP-SC was assessed through its internal consistency as estimated using Cronbach's alpha 23,24 for each dimension or factor, in line with the dimensions proposed by the original model. Since some questionnaire items were worded positively and others negatively, negatively worded items were reverse coded so that in all cases a higher score would indicate a positive response 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Th is fi nding of low internal consistency for the dimension of Staffi ng has also been found in almost all other studies using HSOPSC outside of the US. As in our study, for example, UK and Japanese authors found Staffi ng to be the sole dimension lacking an acceptable level of internal consistency 12,24 . Even in the US, repeat multilevel psychometric survey analysis found Staffi ng to have the lowest Cronbach alpha value of all 12 dimensions in a sample of 331 USA hospitals 25,26 .…”
Section: Discussionmentioning
confidence: 83%
“…Nonpunitive Response to Error was the dimension with the lowest percentage of positive responses not only in our sample, but also in most other studies using the HSOPSC [8][9][10][11][12][13][14]24,30,31 . Our sample, as compared to the US, fell particularly far behind in this dimension, which suggests the infl uence of specifi c diff erences between the two cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation